Water Use in Global Livestock Production—Opportunities and Constraints for Increasing Water Productivity. Issue 12 (11th December 2020) - Heinke, Jens; Lannerstad, Mats; Gerten, Dieter; Havlík, Petr; Herrero, Mario; Notenbaert, An Maria Omer; Hoff, Holger; Müller, Christoph
Abstract: Increasing population, change in consumption habits, and climate change will likely increase the competition for freshwater resources in the future. Exploring ways to improve water productivity especially in food and livestock systems is important for tackling the future water challenge. Here we combine detailed data on feed use and livestock production with Food and Agriculture Organization of the United Nations (FAO) statistics and process‐based crop‐water model simulations to comprehensively assess water use and water productivity in the global livestock sector. We estimate that, annually, 4, 387 km 3 of blue and green water is used for the production of livestock feed, equaling about 41% of total agricultural water use. Livestock water productivity (LWP; protein produced per m 3 of water) differs by several orders of magnitude between livestock types, regions, and production systems, indicating a large potential for improvements. For pigs and broilers, we identify large opportunities to increase LWP by increasing both feed water productivity (FWP; feed produced per m 3 of water) and feed use efficiency (FUE; protein produced per kg of feed) through better crop and livestock management. Even larger opportunities to increase FUE exist for ruminants, while the overall potential to increase their FWP is low. Substantial improvements of FUE can be achieved for ruminants by supplementation with feed crops, but the lower FWP of these feed crops compared to grazed biomass limits possible overall improvements of LWP. Therefore, LWP of ruminants, unlike for pigs and poultry, does not always benefit from a trend toward intensification, as this is often accompanied by increasing crop supplementation. Key Points: Annually, 4, 387 km 3 of water is required to produce the feed consumed by the global livestock sector, of which 94% is green water Opportunities for increasing livestock water productivity exist for all livestock types but are particularly large for ruminants Water productivity improvements for ruminants through supplementation with feed crops are constrained by high water cost to produce crops